Evidence of Intracrystalline Mesostructured Porosity in Zeolites by Advanced Gas Sorption, Electron Tomography and Rotation Electron Diffraction. Issue 11 (8th August 2014) - Garcia‐Martinez, Javier; Xiao, Changhong; Cychosz, Katie A.; Li, Kunhao; Wan, Wei; Zou, Xiaodong; Thommes, Matthias
Abstract The small size of micropores (typically <1 nm) in zeolites causes slow diffusion of reactant and product molecules in and out of the pores and negatively impacts the product selectivity of zeolite based catalysts, for example, fluid catalytic cracking (FCC) catalysts. Size‐tailored mesoporosity was introduced into commercial zeolite Y crystals by a simple surfactant‐templating post‐synthetic mesostructuring process. The resulting mesoporous zeolite Y showed significantly improved product selectivity in both laboratory testing and refinery trials. Advanced characterization techniques such as electron tomography, three‐dimensional rotation electron diffraction, and high resolution gas adsorption coupled with hysteresis scanning and density functional theory, unambiguously revealed the intracystalline nature and connectivity of the introduced mesopores. They can be considered as molecular highways that help reactant and product molecules diffuse quickly to and away from the catalytically active sites within the zeolite crystals and, thus, shift the selectivity to favor the production of more of the valuable liquid fuels at reduced yields of coke and unconverted feed.